Mercúrio (Hg), isótopos estáveis (δ15N &δ13C) e recomendações de segurança alimentar para tubarões e peixes pelágicos de nível trófico superior no Oceano Atlântico. - Goyanna, Felipe Augusto de Alencar (2024)
High trophic level predatory ocean fish are used as sentinel species to assess the presence of persistent contaminants in the world's oceans, such as mercury (Hg). In addition, they are species that are consumed globally by humans, who may eventually be exposed to food poisoning. With this in mind, the thesis aims to analyze Hg concentrations and the proportions of nitrogen (15N/14N) and carbon (13C/12C) in relation to a reference standard in oceanic fish species caught in the Equatorial Atlantic Ocean. The first chapter was designed to carry out a broad review across the Atlantic and Mediterranean, in which several publications were selected between 1973 and 2022 were selected, analyzed and duly compiled, with the aim of investigating Hg contamination in nine species of bony fish, Thunnus thynnus, Thunnus albacares, Thunnus obesus, Thunnus atlanticus, Thunnus alalunga, Katsuwonus pelamis, Xiphias gladius, Coryphaena hippurus and Euthynnus alletteratus, as well as two shark species, Prionace glauca and Isurus oxyrinchus. A significant difference was found between sharks and bony fish, with higher Hg concentrations in sharks. The regions of occurrence were divided into four large areas, but no significant differences were observed between regions. Of the species selected, nine had individuals with Hg concentration values that exceeded the safety limits set by health agencies worldwide. The second chapter was designed to report the first record of Hg concentrations and stable isotopes (δ13C and δ15N) in T. alalunga caught in the Western Equatorial Atlantic Ocean, given that it is one of the main tuna species consumed worldwide. It was found that Hg concentrations in T. alalunga, 92% of which are Methyl-Hg, are higher than in other sub-regions of the Atlantic Ocean, despite its smaller body size. The Hg concentrations found are similar to those in the Pacific and Indian Oceans, but lower than those in the Mediterranean. These results are discussed considering the possible differences in stable isotope values (δ15N and δ13C) of T. alalunga populations from various oceanic areas and in comparison with other tuna species around the world. The third chapter is designed to report Hg and stable isotope (δ15N and δ13C) analyses, as well as present consumption recommendations in eight species of predatory oceanic fish caught in the Western Equatorial Atlantic Ocean. Significant differences in Hg and isotope concentrations were found between species. Hg concentrations were highest in I. oxyrinchus, X. gladius and P. glauca, respectively, intermediate in T. alalunga, Istiophorus albicans and T. obesus, while Hg concentrations were lowest in T. albacares and C. hippurus. The highest δ15N values were observed in I. oxyrinchus, X. gladius and P. glauca, compared to C. hippurus, I. albicans and T. albacares, which showed the lowest values. Intermediate values were observed in T. obesus and T. alalunga. The highest δ13C values were observed in C. hippurus compared to T. alalunga, P. glauca and X. gladius. Only I. oxyrinchus, P. glauca and X. gladius exceeded the regional maximum limit of 1,000 ng.g-1 of Hg established by Brazilian legislation. Finally, recommendations for monthly consumption by humans were made for each species studied. The average safe consumption values ranged from 22.3 ± 23.6 g.day-1 for adults to 4.8 ± 5.0 g day-1 for children in general consumers. The consumption rate was higher in T. albacares and C. hippurus, lower in I. oxyrinchus and X. gladius. The estimated number of meals per month ranged from 0 to 11, considering a portion of 150 and 75 g for adults and children, respectively. Children should avoid eating X. gladius and I. oxyrinchus.